Association of prenatal exposure to polybrominated diphenyl ethers at low levels with adiposity measures in children up to 6 years. (September 2022) - Chen, Yafei; Wang, Ziliang; Fang, Guanghong; Miao, Maohua; Liang, Hong; Chen, Yao; Luan, Min; Liu, Xiaofang; Wen, Sheng; Chen, Aimin; Yuan, Wei
Abstract: The effects of prenatal PBDEs exposure, especially at low levels, on childhood obesity are scarce. No previous studies have investigated the effect modification by breastfeeding on the associations of PBDEs exposure with childhood obesity. We aimed to investigate the associations of prenatal PBDEs exposure with adiposity measures in children up to 6 years, and the effect modification by breastfeeding. Participants were mother-child pairs from the Shanghai-Minhang Birth Cohort study. Nine PBDE congeners were assessed in cord blood plasma. We obtained information about child weight (0–6 years), height (0.5–6 years), arm circumference (0–6 years), and waist circumference (0–6 years) at each follow-up visit. Breastfeeding duration was collected when children were aged 1 year and was categorized as short (≤6 months) and adequate (>6 months). Multiple linear regression models were used to examine the associations of PBDE concentrations with adiposity measures of the children at each age. Generalized estimating equation (GEE) models were used to estimate the overall associations of PBDEs exposure with adiposity measures. We examined the effect modification by breastfeeding using stratified analyses and by including interaction terms into GEE models. For boys, there was a general profile of positive associations of several PBDE congeners exposure with adiposity measures. Especially, boys with higher BDE-153 concentration had higher adiposity measures at each time point. For girls, we also found positive associations of BDE-100 and -153 exposure with adiposity measures. The GEE models showed consistent patterns for BDE-153 in boys and for BDE-100 and -153 in girls. In breastfeeding-stratified analyses, stronger associations of PBDEs exposure with adiposity measures were generally found in children who were shortly breastfed. Our findings suggest that prenatal exposure to PBDEs at low levels may influence childhood adiposity measures, and the potential effects of PBDEs were attenuated by adequate breastfeeding. Graphical abstract: Fig. 1 Association between PBDEs in cord plasma and repeated child adiposity measures of boys up to 6 years using GEE models.Fig. 2 Association between PBDEs in cord plasma and repeated child adiposity measures of girls up to 6 years using GEE models. Image 1 Highlights: BDE-153 level was positively associated with boys' adiposity measures. BDE-100 and -153 levels were positively associated with girls' adiposity measures. The potential effects of PBDEs were attenuated by adequate breastfeeding.